Preparation and characterization of fibrous chitosan-glued phosphate glass fiber scaffolds for bone regeneration - Zheng, Kai; Wu, Zhaoying; Wei, Jie; Russel, Christian; Liang, Wen; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2015)
Phosphate glass fibers (PGF) have emerged as promising building blocks for constructing bone scaffolds. In this study, fibrous scaffolds (PGFS) were fabricated using a facile binding method at room temperature. PGFS exhibited an extracellular matrix-like morphology and were composed of PGF as matrix and chitosan as the natural binding glue. They showed an interconnected porous structure with a porosity of 87 % and pore size of 100–500 µm. PGFS exhibited the typical compressive stress–strain behaviour of highly porous, low-density, open-cell scaffolds. Their yield stress and modulus were 0.38 and 2.84 MPa, respectively, with the strength being higher than the lower bound of the compressive strength of cancellous bone. PGFS were degradable and the weight loss was about 25 % after immersion in stimulated body fluid (SBF) for 28 days. In addition, the yield stress and the modulus decreased with increasing immersion time in SBF. Apatite formation could be detected on the surface of PGFS within 7 days of immersion in SBF. MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay indicated that PGFS were non-cytotoxic against bone marrow stromal cells (bMSCs) after culture for up to 72 h. These results suggest that PGFS could be promising scaffolds for bone regeneration applications.